2018
DOI: 10.1016/j.ijscr.2018.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Juxta-adrenal schwannoma presenting as a giant adrenal tumor: A case report and a literature review

Abstract: HighlightsRetroperitoneal schwannomas (RS) are rare, benign tumors that originate in the neural sheath.RS can be misdiagnosed preoperatively, especially when they stick to other structures (the adrenal in our case).Complete surgical resection is the treatment of choice and open surgery is the safest option when we have big tumors.Histology and Immunohistochemistry confirm the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Malignant schwannomas have a poor prognosis and a high recurrence rate, so early diagnosis is important while emphasizing the necessity of close postoperative follow-up ( 29 ). We should know that regardless of the nature of the tumor, the difficulty of surgery is closely related to the size of the mass and adjacent adhesions, so the importance of early surgery is emphasized instead of only considering the surgical technique ( 30 ). Our study confirmed that benign tumors with large size and adjacent complex vessels can still be completely resected with a satisfactory prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant schwannomas have a poor prognosis and a high recurrence rate, so early diagnosis is important while emphasizing the necessity of close postoperative follow-up ( 29 ). We should know that regardless of the nature of the tumor, the difficulty of surgery is closely related to the size of the mass and adjacent adhesions, so the importance of early surgery is emphasized instead of only considering the surgical technique ( 30 ). Our study confirmed that benign tumors with large size and adjacent complex vessels can still be completely resected with a satisfactory prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…AS is a rare incidentaloma found in the adrenal medulla, and fewer than 100 cases have been reported to date (10,6,(11)(12)(13)(14)(15)(16)(17)(18). The vast majority of AS patients are sporadic.…”
Section: Discussionmentioning
confidence: 99%
“…Standard management of adrenal schwannomas is surgical resection as they are not sensitive to radiotherapy and chemotherapy [4]. e appropriate approach in adrenal schwannomas, either laparoscopic or open, remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the treatment of choice, whenever feasible. Consequently, a definitive diagnosis can only be made upon histological and immunohistochemical studies of the resected lesion [4]. Herein, we report a case of large adrenal schwannoma mimicking adrenal adenoma with a brief review of the literature.…”
Section: Introductionmentioning
confidence: 99%